Visuo-spatial cueing in children with differential reading and spelling profiles - Banfi, Chiara (PLoS One, 2017)
Dyslexia has been claimed to be causally related to deficits in visuo-spatial attention. In particular, inefficient shifting of visual attention during spatial cueing paradigms is assumed to be associated with problems in graphemic parsing during sublexical reading. The current study investigated visuo-spatial attention performance in an exogenous cueing paradigm in a large sample (N = 191) of third and fourth graders with different reading and spelling profiles (controls, isolated reading deficit, isolated spelling deficit, combined deficit in reading and spelling). Once individual variability in reaction times was taken into account by means of z-transformation, a cueing deficit (i.e. no significant difference between valid and invalid trials) was found for children with combined deficits in reading and spelling. However, poor readers without spelling problems showed a cueing effect comparable to controls, but exhibited a particularly strong right-over-left advantage (position effect). Isolated poor spellers showed a significant cueing effect, but no position effect. While we replicated earlier findings of a reduced cueing effect among poor nonword readers (indicating deficits in sublexical processing), we also found a reduced cueing effect among children with particularly poor orthographic spelling (indicating deficits in lexical processing). Thus, earlier claims of a specific association with nonword reading could not be confirmed. Controlling for ADHD-symptoms reported in a parental questionnaire did not impact on the statistical analysis, indicating that cueing deficits are not caused by more general attentional limitations. Between 31 and 48% of participants in the three reading and/or spelling deficit groups as well as 32% of the control group showed reduced spatial cueing. These findings indicate a significant, but moderate association between certain aspects of visuo-spatial attention and subcomponents of written language processing, the causal status of which is yet unclear.